Ethical clinical translation of stem cell interventions for neurologic disease. (17th January 2017) - Cote, David J.; Bredenoord, Annelien L.; Smith, Timothy R.; Ammirati, Mario; Brennum, Jannick; Mendez, Ivar; Ammar, Ahmed S.; Balak, Naci; Bolles, Gene; Esene, Ignatius Ngene; Mathiesen, Tiit; Broekman, Marike L.
Abstract : The application of stem cell transplants in clinical practice has increased in frequency in recent years. Many of the stem cell transplants in neurologic diseases, including stroke, Parkinson disease, spinal cord injury, and demyelinating diseases, are unproven—they have not been tested in prospective, controlled clinical trials and have not become accepted therapies. Stem cell transplant procedures currently being carried out have therapeutic aims, but are frequently experimental and unregulated, and could potentially put patients at risk. In some cases, patients undergoing such operations are not included in a clinical trial, and do not provide genuinely informed consent. For these reasons and others, some current stem cell interventions for neurologic diseases are ethically dubious and could jeopardize progress in the field. We provide discussion points for the evaluation of new stem cell interventions for neurologic disease, based primarily on the new Guidelines for Stem Cell Research and Clinical Translation released by the International Society for Stem Cell Research in May 2016. Important considerations in the ethical translation of stem cells to clinical practice include regulatory oversight, conflicts of interest, data sharing, the nature of investigation (e.g., within vs outside of a clinical trial), informed consent, risk-benefit ratios, the therapeutic misconception, and patient vulnerability. To help guide the translation of stem cells from the laboratory into the neurosurgical clinic in an ethically sound manner, we present an ethical discussion of these major issues at stake in the field of stem cell clinical research for neurologic disease.